The Role of Students in Islamic Politics: Challenges and Opportunities in the Era of Modernisation - aditya, Aditya Purnadani; Fahrudin, Fahrudin; Jaenuri, Jaenuri (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2024)
Students have a role as agents of change as activists for the country, students who are faced with various challenges in this modernisation era have many challenges and also increasingly complex demands.  The development of technology has a big impact at this time. Students continue to strive to overcome problems in the development of this nation. In our country, students play many roles in the political world including (1) Awareness of politics and education, (2) Advocacy of social justice, and (3) Moral guardians in the political world. However, students are still faced with various challenges in this global era related to their status as Muslim intellectuals. The challenge is the lack of understanding from the Muslim community about the principles of Islam.